2019
DOI: 10.1136/bmjopen-2018-028011
|View full text |Cite
|
Sign up to set email alerts
|

Dose–response associations between metabolic indexes and the risk of comorbid type 2 diabetes mellitus among rheumatoid arthritis patients from Northern China: a case–control study

Abstract: ObjectiveTo investigate whether there were any differences in the patterns of metabolic abnormalities between patients with rheumatoid arthritis (RA) with comorbid type 2 diabetes mellitus (T2DM) and other populations, and to plot the dose–response relationships between metabolic indexes and the risk of comorbid T2DM among patients with RA.Design and settingThis is a retrospective case–control study using electronic medical records (EMRs). Patients with RA and/or T2DM or controls who were admitted to the First… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Importantly, using the drawn dose–response curves, we could calculate the risks of developing stroke and subsequent mortality at any specific LAD or LAD/BSA values, which would facilitate risk assessment and individualised management strategies. 30 Above findings implied that close monitoring of echocardiographic LAD increment might add predictive information in the evaluation of stroke and its mortality, which needed to be validated through replication in other populations. However, Mosquera et al found that LAD/BSA raised the risk of stroke in 50.7% per 1 cm/m 2 increment in bivariate analysis, which association disappeared after multivariate regression.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, using the drawn dose–response curves, we could calculate the risks of developing stroke and subsequent mortality at any specific LAD or LAD/BSA values, which would facilitate risk assessment and individualised management strategies. 30 Above findings implied that close monitoring of echocardiographic LAD increment might add predictive information in the evaluation of stroke and its mortality, which needed to be validated through replication in other populations. However, Mosquera et al found that LAD/BSA raised the risk of stroke in 50.7% per 1 cm/m 2 increment in bivariate analysis, which association disappeared after multivariate regression.…”
Section: Discussionmentioning
confidence: 99%
“…macro provided by Desquilbet and Mariotti 23 and had been previously applied in one of my previous articles. 24 Both the overall associations and non-linear associations between NC or NHR and odds of IS were examined. If the test for the overall association between NC or NHR and the odds of IS was statistically significant, NC or NHR was significantly associated with IS, regardless of the shape of the associations.…”
Section: Methodsmentioning
confidence: 99%